2007
DOI: 10.1590/s0036-46652007000600002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of toxocara infection in children attended by the health public service of Maringá, south Brazil

Abstract: SUMMARYThe lack of specific laboratorial diagnosis methods and precise symptoms makes the toxocariasis a neglected disease in Public Health Services. This study aims to determine the frequency of Toxocara spp. infection in children attended by the Health Public Service of Hospital Municipal de Maringá, South Brazil. To evaluate the association of epidemiological and clinical data, an observational and cross-section study was carried out. From 14,690 attended children/year aged from seven month to 12 years old,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
42
2
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 31 publications
13
42
2
17
Order By: Relevance
“…Previous studies in this region have reported that eosinophilia is present in 7.8% (30/386) 1,5,14,15,17,18 . In this study, we have observed two cases of moderate eosinophilia in patients with anti-Toxocara spp.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Previous studies in this region have reported that eosinophilia is present in 7.8% (30/386) 1,5,14,15,17,18 . In this study, we have observed two cases of moderate eosinophilia in patients with anti-Toxocara spp.…”
Section: Discussionmentioning
confidence: 79%
“…Previous seroepidemiological studies involving children attending regional BHUs in the Brazilian state of Paraná have reported seropositivity rates between 32.2% and 56.0% 1,5,14,15,17,18 . However, in our study, only seven out of 167 children (4.2%) showed anti-Toxocara spp.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations